Diagnosis of composite materials in aircraft applications: towards a UAV active thermography inspection approach - Alhammad, Muflih; Avdelidis, Nicolas P.; Deane, Shakeb; Ibarra-Castanedo, Clemente; Pant, Shashank; Nooralishahi, Parham; Ahmadi, Mohammad; Genest, Marc; Zolotas, Argyrios; Zanotti Fragonara, Luca; Valdes, Julio J.; Maldague, Xavier P. (Society of Photo-Optical Instrumentation Engineers (SPIE), 2021)
Diagnosis and prognosis of failures for aircrafts’ integrity are some of the most important regular functionalities in complex and safety-critical aircraft structures. Further, development of failure diagnostic tools such as Non-Destructive Testing (NDT) techniques, in particular, for aircraft composite materials, has been seen as a subject of intensive research over the last decades. The need for diagnostic and prognostic tools for composite materials in aircraft applications rises and draws increasing attention. Yet, there is still an ongoing need for developing new failure diagnostic tools to respond to the rapid industrial development and complex machine design. Such tools will ease the early detection and isolation of developing defects and the prediction of damages propagation; thus allowing for early implementation of preventive maintenance and serve as a countermeasure to the potential of catastrophic failure. This paper provides a brief literature review of recent research on failure diagnosis of composite materials with an emphasis on the use of active thermography techniques in the aerospace industry. Furthermore, as the use of unmanned aerial vehicles (UAVs) for the remote inspection of large and/or difficult access areas has significantly grown in the last few years thanks to their flexibility of flight and to the possibility to carry one or several measuring sensors, the aim to use a UAV active thermography system for the inspection of large composite aeronautical structures in a continuous dynamic mode is proposed.
Keywords: Failure diagnosis; damage detection; aircraft applications; non-destructive evaluation; UAV; inspections; thermography; imaging